Analysis of Training and Development Implementation to Overcome Resistance to The Use of The E-Patent Application at The Gunungsitoli Idanoi District Office - Laowo, Asni Jeweliska; Hulu, Fatolosa; Telaumbanua, Eliagus; Zebua, Serniati (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
This study analyzes the implementation of training and development programs to address resistance to the use of the E-Patent application at the Gunungsitoli Idanoi District Office. A qualitative approach was employed, with data collected through observation, interviews, and documentation. The data were then analyzed descriptively to provide a comprehensive understanding of the phenomenon. The findings reveal that training and development initiatives have contributed to improving employees’ understanding and skills in operating the application. However, the improvements remain relatively modest, indicating the need for continuous and more structured training programs. Resistance was identified in both overt and covert forms, including reluctance to adopt new systems, lack of confidence, and dependence on old work routines. These challenges suggest that training and development are not only technical solutions but also strategic tools for change management. Therefore, effective training must be designed to foster adaptive attitudes, enhance motivation, and build a culture of innovation in public services. The study emphasizes the importance of integrating employee development into organizational change strategies to ensure the successful adoption of digital transformation in local government.